Peluang dan Tantangan Generasi Muda Menuju Pertanian Bekelanjutan: Opportunities and Challenges for the Young Generation Towards Sustainable Agriculture - Zidan, Zacky; Rozaki, Zuhud; Wulandari, Retno; Distrianada, Ridho Ikbar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
This research explains the role of the younger generation in facing the increasingly complex challenges of agriculture, especially in the context of climate change. Focusing on technological innovation, this research outlines how youth engagement can be a key driver of positive transformation in the agricultural sector. Through innovative approaches, such as the application of advanced technologies and sustainable practices, the younger generation is expected to increase agricultural productivity and resilience. The research details the impacts of climate change on agriculture and identifies innovative opportunities that the younger generation can take to address the challenges. In the context of climate change and exposure to global markets, the younger generation is identified as a potential agent of change. A key focus was to explore how technology can improve agricultural efficiency, productivity and resilience. The younger generation is expected to address environmental challenges and meet the demands of a dynamically changing global market. The results of this study provide insights into the transformational potential of the younger generation in shaping a sustainable and globally relevant future for agriculture.